If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 3 + -2s Solving -3 = 3 + -2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '2s' to each side of the equation. -3 + 2s = 3 + -2s + 2s Combine like terms: -2s + 2s = 0 -3 + 2s = 3 + 0 -3 + 2s = 3 Add '3' to each side of the equation. -3 + 3 + 2s = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 2s = 3 + 3 2s = 3 + 3 Combine like terms: 3 + 3 = 6 2s = 6 Divide each side by '2'. s = 3 Simplifying s = 3
| 20log(x)=-.662 | | -16t^2+28t=-250 | | x+(2x)+(x-7)=77 | | 2=6-2j | | (x-1)(x+2)=5(x-1) | | 91=n+(4n-2)+(5n-7) | | x^2+56x-18=0 | | 5(x+3)x=3 | | 100m^2=9 | | 2x^2+25-21x=0 | | -11/2=t/2-1/4(-6t-2) | | 4y+16=2y+10 | | S^4+7s^3+14s^2+(8+9.65)*s+3*9.65=0 | | -4.9t^2+18t=10 | | 7x^2=-105 | | 3x^2-66=-27x | | (29b-8)-7(4b+1)=-2 | | 54=n+(3n+2)+(4n-4) | | 2/3(-100-2x)=0 | | 2p-3=1 | | 40+5L=200 | | (8x+17y)+(11x-8y)= | | 20+4L=50 | | -100x^4+30x^3+40x^2+50x+40=0 | | (b*b)+3+2(b*b)+4-7= | | -16t^2+105t=63.2 | | a+36=120 | | -9y^2=-144 | | W^2-10w=250 | | x-3.4=9.24 | | 3(2x-9)=x+44 | | F(X+1)=2(X+16) |